A rare case of surgical treatment of a patient with gastric cancer with Cartagener syndrome - S. G. Afanasyev; A. Yu. Dobrodeev; D. N. Kostromitsky; Yu. V. Rudyk; M. Yu. Grishchenko; E. S. Drozdov; E. N. Samtsov; U. B. Urmonov (Вестник хирургии имени И.И. Грекова)
Kartagener Syndrome (CS) is a rare autosomal recessive disease that is a part of primary ciliary dyskinesia (PCD), and is characterized by a triad of syndrome including bronchiectasis, polysinusitis and a complete mirror arrangement of the internal organs of the chest and abdominal cavities (situs inversus). In most patients, bronchiectasis in the lungs develops from the first years of life and progresses in time. The tardy diagnostic leads to a poor prognosis of the disease and adduce the development of persistent violations of the function of external respiration. Most often, patients with CS are observed by physicians and pulmonologists from early childhood, since respiratory infections often require annual hospitalization in specialized medical institutions due to abnormalities of the ciliary epithelium of the respiratory tract. However, to date, there are no generally accepted recommendations for the management and treatment of patients in this category. This article describes the case of a newly diagnosed CS in an older patient undergoing surgical treatment for gastric cancer. Despite the pronounced concomitant pathology on the part of the bronchopulmonary system, the perioperative period in the patient proceeded relatively satisfactorily and did not entail an increase in the length of hospitalization.